اساس وحدود سلطة الإدارة في إنهاء العقد الإداري - Kafi, Walid Khedir (Gezira Journal of Economic and Social Sciences; مجلد 13 عدد 1 (2022), 2022)
يعتبر العقد الإداري من الاعمال القانونية التي تقوم بها الإدارة العامة، ولذلك لابد ان تكون للإدارة سلطات وصلاحية اكبر في العقد الإداري ، وبالتالي لابد أن يكون للإدارة اساس قانوني تستند عليه، وكذلك حدود لسلطاتها الكبيرة في العقد الإداري، تهدف هذه الدراسة  لبيان مفهوم العقد الإداري، وتوضيح الاساس القانوني  لسلطة  الإدارة في إنهاء العقد الإداري، توضيح حدود سلطة الإدارة في إنهاء العقد الإداري،وتكمن مشكلة الدراسة في امتلاك الإدارة صلاحية الإنهاء الانفرادي للعقد، وحدود هذه الصلاحية، وكان اعتماد المنهج الوصفي التحليلي والاستقرائي، توصلت هذه الدراسة إلي عدد من النتائج والتوصيات ، من اهم هذه النتائج ان سلطة الإدارة في الإنهاء للعقد الإداري من اخطر السلطات التي قد تمارسها الجهة الإدارية المتعاقدة ضد المتعاقد معها، وإن سلطة الإنهاء ليست مطلقة بل مقيدة بضوابط وشروط لابد من توافرها حتي تستطيع الإدارة اللجوء اليها وتطبيقها،كما أوصت الدراسةبضرورة قصر سلطة الإدارة الرقابية علي العقد في الاشراف والتوجيه دون تعديل شروط العقد ،على السلطة القضائية القيام بالرقابة على قرارات الإدارة في توقيع الجزاء على الإدارات التي تتجاوز حدود السلطات الممنوحة لها. Abstract : The administrative contract is considered one of the legal acts carried out by the public administration, and therefore the administration must have greater powers and authority in the administrative contract, and therefore the administration must have a legal basis on which to rely, as well as limits to its great powers in the administrative contract. This study aims to clarify the concept of the administrative contract, Clarifying the legal basis for the administration’s authority to terminate the administrative contract, clarifying the limits of the administration’s authority to terminate the administrative contract, and the problem of the study lies in the administration’s having the authority to unilaterally terminate the contract, and the limits of this validity. Among the most important of these results is that the authority of the administration to terminate the administrative contract is one of the most dangerous powers that the contracting administrative authority may exercise against the contractor with it, and that the termination authority is not absolute, but rather restricted by controls and conditions that must be met so that the administration can resort to and apply them, as the study recommended the necessity of limiting the authority of the administration In supervising and directing the contract without modifying the terms of the contract, the judicial authority must monitor the management’s decisions in imposing the penalty on the Departments that exceed the limits of the powers granted to them.